Within-person relationship between self-efficacy and performance across trials: Effect of task objective and task type - Hepler, T. J.; Ritchie, J.; Hill, C. R. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Self-efficacy has been shown to be a consistent, positive predictor of between-persons performance in sport. However, there have been equivocal results regarding the influence of self-efficacy on a person`s performance over time. This study investigated the influence of self-efficacy on motor skill performance across trials with respect to two different task objectives and task types. METHODS: Participants (N.=84) performed 4 blocks of 10 trials of a dart throwing (closed skill) and a hitting (open skill) task under 2 different task objectives: competitive and goal-striving. For the goal-striving condition, success was defined as reaching a predetermined performance level. The competitive condition involved competing against an opponent. RESULTS: Hierarchical linear modeling was used to examine the influence of past performance and self-efficacy on the within-person performance across multiple trials. Previous performance was negatively related with subsequent performance on all conditions. Self-efficacy was not a significant predictor of performance on any of the conditions. CONCLUSIONS: While task objective and task type did not moderate the efficacy-performance relationship in the current study, it is important to consider the role of other moderators in future research.